127 Audit of poor response to botulinum toxin in cervical dystonia. Issue 12 (14th November 2019) - Tucker, Harry; Osei-Poku, Foster; Ashton, Diane; Lally, Rachael; Alty, Jane; Kobylecki, Christopher
Abstract : Background: Botulinum toxin (BoNT) is an effective first-line treatment for cervical dystonia. However, secondary non responsiveness to BoNT treatment remains a key reason for a discontinuation rate of 20%. In 2016 the British Neurotoxin Network (BNN) published recommendations for the management of cervical dystonia patients with poor response to BoNT treatment. Aims: To compare management of patients with secondary non responsiveness in two regional neuroscience centres with the BNN guidelines. Methods: We retrospectively analysed 68 patients with cervical dystonia who met criteria for secondary non responsiveness to BoNT-A treatment. Results: Suboptimal response to BoNT-A was recorded in 37 patients (54%), whilst 31 (46%) had no therapeutic response. In the 'suboptimal response' group, 21 (57%) had a subsequent good therapeutic response with adjustment of dose, muscle selection and injection technique and continued BoNT-A treatment. Of the remainder, 6 (38%) were switched to BoNT-B and 7 (44%) were referred for Deep Brain Stimulation surgery. In the 'no response' group 6 patients (19%) had a good therapeutic response with adjustments of dose, muscle selection and injection technique and continued BoNT-A treatment. In this group 22 patients (71%) were assessed for BoNT-A resistance, which was confirmed in 8 (36%). Conclusion: Our audit shows the importance of careful assessment of patients with cervical dystonia presenting with secondary non-reponsiveness to BoNT-A therapy. The BNN recommendations provide a useful framework for improving dystonia treatment.